A Global Assessment of Copper, Zinc, and Lead Isotopes in Mineral Dust Sources and Aerosols - Schleicher, Nina J.; Dong, Shuofei; Packman, Hollie; Little, Susan H.; Ochoa Gonzalez, Raquel; Najorka, Jens; Sun, Youbin; Weiss, Dominik J. (Frontiers in Earth Science, 2020)
The stable isotope compositions of Cu and Zn in major geochemical reservoirs is increasingly studied with the aim to develop these isotope systems as novel tools to study their global biogeochemical cycles. The objectives of the present study were in particular (i) to constrain further the range of Cu, Zn, and Pb isotope compositions of mineral dust by analysing samples from major mineral dust sources in Asia and Africa (Chinese Loess Plateau, Chinese deserts, Thar desert, Sahel region) and (ii) to assess the impacts of human activities on the isotope composition of aerosols by synthesising published Cu and Zn isotope compositions in aerosols and natural and anthropogenic sources. For the newly analysed mineral dust areas in Asia and Africa, d65CuNIST-976 values range from -0.54‰ to +0.52‰, d66ZnJMC-Lyon values from -0.07‰ to +0.57‰, and 206Pb/204Pb values from 18.522 to 19.696. We find a significant geographic control with samples collected from the Thar Desert having the heaviest isotopic compositions (d65CuNIST-976 = +0.48 ± 0.06‰, d66ZnJMC-Lyon = +0.49 ± 0.11‰) and samples from the Sahel and the Badain Jaran desert having the lightest Zn isotope composition (d66ZnJMC-Lyon = +0.19 ± 0.15‰ and +0.07 ± 0.07‰, respectively). We find important variations between different particle size fractions with heavier isotopic compositions in the smallest and largest particle size fractions and lighter compositions in the mid particle size fractions. Associations with the mineralogical composition are less clear. Newly analysed aerosol samples for Beijing and Xi’an have d65CuNIST-976 values of +0.29 ± 0.19‰ and +0.16 ± 0.04‰, d66ZnJMC-Lyon values of -0.36 ± 0.04‰ and +0.02 ± 0.06‰, and 206Pb/204Pb values of 18.129 ± 0.003 and 18.031 ± 0.003, respectively. Based on the synthesis of published and novel data, we suggest ranges and mean values for the isotopic composition of mineral dust from selected locations in Asia and Africa and of anthropogenic sources such as non-exhaust traffic emissions, combustion, electroplating and galvanization. This should serve as a valuable reference for future studies. This paper demonstrates univocally that human activity introduces a wide range of Zn isotope compositions into the atmospheric environment and, thus, impacts its biogeochemical cycle.